A Study on How the Features and Design of Social Media, Emotions and Behavior, and Advertising Affect Impulse Buying - Khadijah, Alifa (Journal of Business, Management, and Social Studies, 2022)
The purpose of this study is to identify and evaluate how marketers use social media to capitalize on impulse purchases. This study focuses on the Indonesian e-commerce market to investigate how social media affects impulse buying. This study will also examine and make an effort to demonstrate the connection between the misuse of social media and how it led to impulsive choices or purchases. Data from a survey of 71 social media users in Jakarta was used to test the proposed model and hypotheses. Statistical analyses performed towards the data proved that there is a significant effect of social media emotions and behavior on impulse buying. However, social media advertisement as well as design and features do not have a positive impact on impulse buying. This is one of the few investigations to study features and design in a social media context along with emotions and behavior as well as advertising affecting impulse buying.